2023
DOI: 10.1590/2675-2824071.2206icas
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic conditions of the continental slope and deep waters in Santos Basin: the SANSED cruise (winter 2019)

Abstract: This work describes the circulation over the continental slope and the São Paulo Plateau in the Santos Basin during the SANSED winter 2019 survey. The cruise consisted of four legs in the period between June, 11 and August, 03 2019. The observed circulation is dominated by the Atlantic southwestern boundary current regime and remotely-generated anticyclones and cyclones. The former is composed by the Brazil Current, the Intermediate Western Boundary Current and their mesoscale meanders; the latter are 300km vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the first 15 days of larval experiment, the CFE growth is quasi-stationary and as it increases it is advected southward by the mean water flow due to the Brazil Current. As mentioned by [ 75 ], the offshore displacement of the CFE is also intricately intertwined with complex interactions involving other eddies formed within the region, as well as those that arrived in the region. This pattern is illustrated in Fig 6 , where a high density of red markers at 24.2°S and 42°W represents the initial growth in a stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…In the first 15 days of larval experiment, the CFE growth is quasi-stationary and as it increases it is advected southward by the mean water flow due to the Brazil Current. As mentioned by [ 75 ], the offshore displacement of the CFE is also intricately intertwined with complex interactions involving other eddies formed within the region, as well as those that arrived in the region. This pattern is illustrated in Fig 6 , where a high density of red markers at 24.2°S and 42°W represents the initial growth in a stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…The shallow and deep-water meteoceanographic processes that influence Santos Basin geomorphology and sediment composition, like waves, currents, and water masses, are thoroughly discussed by Dottori et al (2023) and Silveira et al (2023).…”
Section: Environmental Settingmentioning
confidence: 99%
“…They showed that the continental shelf can be divided into two sectors with distinct characteristics in relation to the São Sebastião areas: (1) in the Southwestern sector, the presence of Subtropical Shelf Water (STSW) modulates the hydrographic parameters, and (2), the Northeastern sector where the uplifting of the South Atlantic Central Water was the dominant process (Dottori et al, 2023). On the slope and São Paulo plateau, hydrographic circulation is dominated by both the Atlantic southwestern boundary (ASB) current regime and the remotely generated eddies (Silveira et al, 2023). The Brazilian Current, the Intermediate Western Boundary Current, and their mesoscale meanders form the ASB, whereas the eddies originate on the eastern side of the South Atlantic Basin.…”
Section: Hydrographic Conditionsmentioning
confidence: 99%